The regularity of the space of germs of Fréchet valued holomorphic functions and the mixed Hartog’s theorem - Thai Thuan Quang (My University, 2006)
The regularity of the space of germs of Fréchet valued holomorphic functions and the mixed Hartog’s theorem
Keywords: Space of germs; Holomorphic functions; Hartog’s theorem